Reviewing the past to learn in the future: making sense of design errors and failures in construction - Love, Peter; Lopez, Robert; Edwards, David (Taylor & Francis, 2013)
Design errors can severely jeopardise safety and contribute to failures in construction and engineering projects. Such failures can have devastating economic, environmental and social consequences. Significant efforts have been made to reduce the incidence of failures through learning from previous disasters and events by modifying building and engineering codes and standards accordingly. Design errors, however, remain an innate feature of construction and engineering projects despite the considerable amount of knowledge that has been accumulated to date. Most errors are identified during construction and require rework, but there is always a potential for some to remain undetected and contribute to failure, and as a result potentially contribute to accidents and loss of life. An examination of the literature research suggests that a series of pathogenic influences contribute to errors and failure. Thus, this paper article examines the circumstances and issues that contributed to a series of construction and engineering failures to enable development of a learning framework that can be used to mitigate design errors and potential failures and accidents.